Resilience, sleep quality and sleepiness in Peruvian medical students: a multicenter study - Zila-Velasque, Jean Pierre; Grados-Espinoza, Pamela; Chuquineyra, Brenda Sofia-Caira; Diaz-Vargas, Mills; Sierra Calderón, Gabriela Stefanie; Choquegonza, Sthefanny; Temoche-Rivas, Mario S.; Siguas Peixoto, Karina; Valladares-Garrido, Mario J.; Failoc-Rojas, Virgilio E. (Frontiers in Psychiatry, 2024)
Background: Resilience can mitigate the negative impact produced by the COVID-19 pandemic.Medical students endure significant academic stress, so adjusting to sudden changes can present greater mental health challenges. The aim is to identify the level and prevalence of resilience and to know what are the educational variables and is sleep quality associated with resilience.: A cross-sectional study was conducted using an online questionnaire. The survey was elaborated in Google Forms and shared through social networks. The outcome was resilience, measured with the Connor Davidson Resilience Scale. Its association was assessed with sleep quality (measured with the Pittsburgh Sleep Quality Index), daytime sleepiness (measured with the Epworth Sleepiness Scale), and selected academic/sociodemographic variables. Generalized linear models were used to identify the association between the variables. Results: Of 1277 participants, 35.7% experienced high resilience. Poor sleep quality and sleepiness were present in 88.4% and 36.0% of students, respectively. High resilience was associated with good sleep quality (